The Brazilian Navy naval refit policy, 1904-1945 - Waldmann Júnior, Ludolf (2020)
The Brazilian Navy has prepared several naval refit programs during the first half of the twentieth century. In 1904 and 1906 ambitious naval programs were approved, however the newly acquired fleet eventually became obsolete before 1914. In the following decades new proposals were made, but the political and economic crisis prevented a naval renewal. The scenario only changed during Vargas Era, when a new naval program was implemented. With the beginning of World War II and the alliance with the United States, the Brazilian fleet was modernized. Our objective is to understand the trajectory and which elements were relevant to the elaboration and approval of the naval renewal programs in this period, taking in account the international and domestic politics as well the organization of the navy.